2020
DOI: 10.1183/23120541.00340-2020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Swedevox registry of continuous positive airway pressure, long-term mechanical ventilator and long-term oxygen therapy

Abstract: BackgroundThe Swedish Registry of Respiratory Failure (Swedevox) collects nationwide data on patients starting continuous positive airway pressure (CPAP) treatment, long-term mechanical ventilator (LTMV) and long-term oxygen therapy (LTOT). We validated key information in Swedevox against source data from medical records.MethodsThis was a retrospective validation study of patients starting CPAP (n=175), LTMV (n=177) or LTOT (n=175) across seven centres 2013–2017. Agreement with medical record data was analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In addition, reported Swedevox registry data have a high degree of internal and external validity, as evidenced by an actual validation study that demonstrated > 98% agreement of register data and source data in the medical records. 35 Cross-linkage of our patient data with high-quality socioeconomic data from the nationwide A number of limitations need to be discussed, including a high proportion of patients lost to follow-up (more than 60%), which may have created an important bias in our analysis. solved first, but automated follow-up reporting definitely would increase data capture and would strengthen overall data quality from the registry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reported Swedevox registry data have a high degree of internal and external validity, as evidenced by an actual validation study that demonstrated > 98% agreement of register data and source data in the medical records. 35 Cross-linkage of our patient data with high-quality socioeconomic data from the nationwide A number of limitations need to be discussed, including a high proportion of patients lost to follow-up (more than 60%), which may have created an important bias in our analysis. solved first, but automated follow-up reporting definitely would increase data capture and would strengthen overall data quality from the registry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reported Swedevox registry data have a high degree of internal and external validity, as evidenced by an actual validation study that demonstrated > 98% agreement of register data and source data in the medical records. 35 Cross-linkage of our patient data with high-quality socioeconomic data from the nationwide Swedish Civil Registry and Tax Authorities creates a world-unique database in size and data quality.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of the present study are the large, nationwide cohort of patients treated with LTOT, with complete follow-up using mandatory national registries and high internal and external validity of LTOT data [4,9]. With an estimated completeness of 85-90% the study is population-based in regard to patients starting LTOT.…”
Section: Discussionmentioning
confidence: 99%
“…The following patient level data were collected from Swedevox at the start of LTOT (baseline) [20]: age, gender, forced expiratory volume in one second (FEV 1 ) % of predicted, vital capacity (VC) % of predicted, FEV 1 /VC, arterial oxygen tension (PaO 2 ) and arterial carbon dioxide tension (PaCO 2 ) while breathing air and oxygen. The data in Swedevox, including the ILD diagnosis, spirometry and blood gases, were recently validated with high concordance with medical records [22]. Data on dispensed drug prescriptions were obtained from the Swedish Prescribed Drug Register, which includes all dispensed prescriptions during outpatient care nationwide.…”
Section: Assessmentsmentioning
confidence: 99%